1987
DOI: 10.1016/0014-5793(87)80654-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lectins, cell‐cell recognition and infectious disease

Abstract: Numerous bacterial strains produce surface lectins, commonly in the form of fimbriae that are filamentous assemblies of protein subunits. Among the best characterized of these are the type 1 (mannose specific) fimbrial lectins of Escherichia coli that consist almost exclusively of one class of subunit with a molecular mass of 17 kDa. They possess an extended combining site corresponding to a trisaccharide and preferentially bind carbohydrate units of oligomannose or hybrid type. Type 1 fimbriae also possess a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
229
0
7

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(239 citation statements)
references
References 51 publications
3
229
0
7
Order By: Relevance
“…Type 1 fimbriae are commonly found and have a similar structure in most enterobacterial genera [15]; it can therefore be expected that the binding activity described here occurs in bacteria other than E. coli.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Type 1 fimbriae are commonly found and have a similar structure in most enterobacterial genera [15]; it can therefore be expected that the binding activity described here occurs in bacteria other than E. coli.…”
Section: Discussionmentioning
confidence: 85%
“…that totally inhibits the binding of type 1 fimbriae to eukaryotic cells and glycoproteins [15], and yeast cell agglutination by type I fimbriae was not inhibited by plasminogen at 100/~g/ml (not shown). On the other hand, treatment of type-l-fimbriated bacteria with activated plasmin (100/zg/ml for 2 h at 37°C) did not influence their ability to agglutinate yeast cells (not shown).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We reviewed the published literature and found that there was strong evidence for a positive link between adherence, the presence of fimbriae, and mannosebinding activity by bacteria (Harper et al, 1978;Ofek and Beachey, 1978;Sharon, 1987Sharon, , 2006. For several (Stepinska and Trafny, 1995;King et al, 2000;McEwan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be due to the presence of an extended FimH binding pocket with multiple subsites corresponding to the size of a trimannose (3M) and, possibly, pentasaccharide (22)(23)(24). Indeed, although some lectins are capable of binding simple monosaccharides, it is rather typical for lectins to bind specifically to complex oligosaccharide ligands that ensure high affinity and specificity for cell-cell or cell-surface interactions (25).…”
mentioning
confidence: 99%